2015
DOI: 10.5507/bp.2013.081
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous silent periods in multiple system atrophy

Abstract: Aim. The cutaneous silent period (CSP) is a spinal inhibitory reflex primarily mediated by A-delta fibers. Prolonged CSPs have been reported in patients with restless legs syndrome (RLS) and idiopathic Parkinson's disease (IPD). Dopaminergic medication normalizes the CSP, concurring with the effect of levodopa on CSPs. To date, CSPs have not been extensively studied in patients with multiple system atrophy (MSA). The purpose of this study was to confirm abnormal CSP findings in a group of MSA patients and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The prolonged duration of CSP in patients with Parkinson’s disease was significantly lower after l -dopa treatment[ 21 ]. Patients with multiple system atrophy also show prolonged CSP duration[ 22 ]. In addition, Han et al found significantly longer CSP duration in patients with restless legs syndrome (RLS), which is considered a central sensitization syndrome[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged duration of CSP in patients with Parkinson’s disease was significantly lower after l -dopa treatment[ 21 ]. Patients with multiple system atrophy also show prolonged CSP duration[ 22 ]. In addition, Han et al found significantly longer CSP duration in patients with restless legs syndrome (RLS), which is considered a central sensitization syndrome[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was normalized after administration of low-dose propranolol in essential tremor 12 . Levodopa did not normalize any of the abnormal CSP parameters in patients with multiple system atrophy whereas; a single dose of levodopa may decrease the CSP duration in in patients with Parkinson's disease 13,14 .…”
Section: Discussionmentioning
confidence: 67%
“…However, the results should be interpreted cautiously because of the low number of subjects in these studies. In contrast, others studies showed delayed and prolonged CuSP in MSA ( Stetkarova et al, 2015 ), probably due to defects in reticulospinal and corticospinal inputs that change spinal excitability ( Eusebio et al, 2007 ).…”
Section: Long Latency Reflex and Cutaneous Silent Periodmentioning
confidence: 88%